Vibration Reduction Design of Marine Planetary Herringbone Gear Transmission Based on Phase Tuning Theory - Zhao Tianyu; Zou Haoran; Wang Sanmin; Li Zhibin (Jixie chuandong)
Planetary herringbone gears are increasingly used in the high-power marine transmission system. In order to meet the noise requirements of transmission system of modern ships, the vibration reduction design of planetary herringbone gear transmission system is not only of practical value, but also of theoretical significance. Aiming at the planetary herringbone gear transmission in the power system of a ship, the analytical expression of the dynamic meshing force between the center gear and the planetary gear is established, and the coupling law between the number of teeth of planetary and center gear, the number of planetary gear and the vibration amplitude caused by the meshing frequency excitation is obtained. Based on the corresponding relationship between the vibration mode caused by time-varying meshing stiffness excitation and the natural vibration mode of the transmission system, and by reasonable design of basic parameters of planetary herringbone gear transmission, a phase tuning vibration reduction design method is proposed to suppress the torsional vibration of the system. The method has been verified to achieve the purpose of suppressing torsional resonance of the central member.